2019
DOI: 10.3390/molecules24234350
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Separation of H2 from CO2 Using a ZIF-8 Membrane by Molecular Simulation and Maxwell-Stefan Model

Abstract: The purification of H2-rich streams using membranes represents an important separation process, particularly important in the viewpoint of pre-combustion CO2 capture. In this study, the separation of H2 from a mixture containing H2 and CO2 using a zeolitic imidazolate framework (ZIF)-8 membrane is proposed from a theoretical point of view. For this purpose, the adsorption and diffusion coefficients of H2 and CO2 were considered by molecular simulation. The adsorption of these gases followed the Langmuir model,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The results ( Figure 2 a) demonstrated that ZIF-8 could adsorb more than 2-fold more heparin compared to ZIF-67 in a pure aqueous solution. The reported BET surface areas for ZIF-8 and ZIF-67 are >1300 and ~316 m 2 /g, respectively [ 31 , 32 ], which are well correlated with their differences in adsorption efficiency. Due to the superior adsorption capabilities of ZIF-8 over ZIF-67, ZIF-8 was selected for further experiments to evaluate adsorption in real samples containing porcine intestinal mucosa.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results ( Figure 2 a) demonstrated that ZIF-8 could adsorb more than 2-fold more heparin compared to ZIF-67 in a pure aqueous solution. The reported BET surface areas for ZIF-8 and ZIF-67 are >1300 and ~316 m 2 /g, respectively [ 31 , 32 ], which are well correlated with their differences in adsorption efficiency. Due to the superior adsorption capabilities of ZIF-8 over ZIF-67, ZIF-8 was selected for further experiments to evaluate adsorption in real samples containing porcine intestinal mucosa.…”
Section: Resultsmentioning
confidence: 99%
“…Zeolite imidazole frameworks (ZIFs) are a new class of MOFs consisting of imidazolate linkers and metal ions. Due to their high surface area, pore volume, thermal and chemical stability, and adaptable functionalization, ZIFs have found applications in various fields as sensors, drug delivery agents, gas separation agents, and electronic device components [ 27 , 28 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…The enhancement factor (EF) of all BZDs was calculated by comparing the extracted analytes concentration with that in the original urine sample. As shown in Table 1 , DZP with the highest log P value (4.02) offers an EF of 30.0, while TRI with the lowest log P value (3.67) gives an EF of 27.8, indicating that the hydrophobic interaction between ZIF-8@Dt-COOH(2×) and BZDs play the key role during the adsorption process given by the hydrophobic characteristics of ZIF-8 [ 39 ]. Additionally, the π–π interaction between the aromatic rings of the BZDs and the ZIF-8 framework is another probable reason for the adsorption.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the diffusion behavior the system was initially equilibrated at 200.0 ps and followed by 1500 ps NVT-MD simulations [53][54][55]. The velocity Verlet algorithm was used to integrate the equations of motion [53].…”
Section: Diffusion Methodsmentioning
confidence: 99%